Synthesis and methods development of adsorbents based on poly (styrene-divinylbenzene) derivatives for solid phase extraction of aromatic compounds - Siregar, Sri Hilma (2005)
In this study, poly (styrene-divinylbenzene) (PS-DVB) adsorbents were synthesized by using suspension polymerization method. The modifications on highly cross-linked porous PS-DVB resin consisted of (i) Friedel-Crafts acylation reaction using stearoyl chloride as an acylation agent to produce PS-DVB heptadecyl ketone, (ii) Chloromethylation reaction to produce chloromethyl PS-DVB in the presence of chloromethyl styrene, and (iii) Williamson ether reaction using sodium metal and octadecanol as reaction agents to produce octadecoxy methyl PS-DVB. The synthesized adsorbents were characterized by Fourier transform infrared (FTIR), scanning electron microscopy (SEM), nitrogen adsorption analysis and thermogravimetric analysis (TGA). Solid phase extraction (SPE) studies of selected organic test compounds, namely nitrobenzene, 2-chlorophenol, benzaldehyde, butyrophenone, and p-cresol were carried out using SPE tubes packed with the synthesized adsorbents. Commercial SPE adsorbents were also used for comparison. The recoveries obtained for the home-made PS-DVB were in the range of 7% to 72% with relative standard deviations of 1% to 10%. Increased percentages of recovery (35%-83%) with the relative standard deviations of 2%-7% were obtained using PSDVB heptadecyl ketone. Highest recovery percentages (67%-100%) were obtained using commercial C18-silica adsorbent. Breakthrough volume determinations for the various adsorbents showed that highest breakthrough volume was achieved for PSDVB heptadecyl ketone adsorbent, i.e. 30.60 mL of 20 ppm nitrobenzene and 20.47 mL of 20 ppm 2-chlorophenol. Lowest breakthrough volume was obtained for octadecoxy methyl PS-DVB adsorbent (1.03 mL of 20 ppm nitrobenzene and 1.00 mL of 20 ppm 2-chlorophenol). PS-DVB heptadecyl ketone has been proven suitable to be used as SPE adsorbent in the future.